2017
DOI: 10.1021/acsnano.7b03826
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Probing of Elastic–Electronic Response to Vacancy Motion in NiO Nanocrystals

Abstract: Measuring the diffusion of ions and vacancies at nanometer length scales is crucial to understanding fundamental mechanisms driving technologies as diverse as batteries, fuel cells, and memristors; yet such measurements remain extremely challenging. Here, we employ a multimodal scanning probe microscopy (SPM) technique to explore the interplay between electronic, elastic, and ionic processes via first-order reversal curve I-V measurements in conjunction with electrochemical strain microscopy (ESM). The techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…In addition, the R-V characteristic between two resistance states (ON-state and OFF-state) is clearly observed at ±5.3 V applied voltage bias (left inset graph of Figure 2d), indicating the formation and deformation of the conducting filament in the nanocrystal via redox reaction occurs at the Pt/NiO interface as described in our previous results. [21] For further test, we observed this on at least twenty NiO nanocrystals taken from the topography image in Figure 2b and we found that the edge resistance is constantly higher than the core resistance (right inset graph of Figure 2d). This suggests that the memristive switching is mainly active at the edge rather than the core of NiO nanocrystals.…”
Section: Non-linear Behavior Of Nio Nanocrystalmentioning
confidence: 67%
See 4 more Smart Citations
“…In addition, the R-V characteristic between two resistance states (ON-state and OFF-state) is clearly observed at ±5.3 V applied voltage bias (left inset graph of Figure 2d), indicating the formation and deformation of the conducting filament in the nanocrystal via redox reaction occurs at the Pt/NiO interface as described in our previous results. [21] For further test, we observed this on at least twenty NiO nanocrystals taken from the topography image in Figure 2b and we found that the edge resistance is constantly higher than the core resistance (right inset graph of Figure 2d). This suggests that the memristive switching is mainly active at the edge rather than the core of NiO nanocrystals.…”
Section: Non-linear Behavior Of Nio Nanocrystalmentioning
confidence: 67%
“…    as shown in our previous work. [21] On the other hand, if the initial state of the nanocrystal is ON-state, then the bias voltage was swept with the order of Figure 1d. The taller the nanocrystal, the higher voltage required to induce the memristive behavior because the field is simply not strong enough to create the modulation due to the migration of the carriers at Pt/NiO interface.…”
Section: Non-linear Behavior Of Nio Nanocrystalmentioning
confidence: 99%
See 3 more Smart Citations